Functional Analysis of Two Divergent C4 Isotypes in the Classical and Lectin Pathways of Complement Activation in the Common Carp (Cyprinus carpio) - Rosli Nehlah; Akira Yamamoto; Takahiro Nagasawa; Tomonori Somamoto; Miki Nakao (Journal of Marine Science and Engineering, 2023)
In the evolution of the complement system, a major humoral innate immune factor, the existence of multiple isotypes of the complement components is considered as a key strategy to enhance innate immune defense. Complement C4 is also diversified in a wide range of vertebrate species including teleost fish, possibly supporting the robust activation mechanism of the complement. To better understand the functional diversity of C4 isotypes in the teleost complement system, two C4 isotypes, C4-1 and C4-2, sharing only 32% amino acid sequence identity, were examined for binding specificities towards model target molecules representing microbe antigens and towards Gram-positive and -negative bacteria. The results suggest that C4-1 and C4-2 behave similarly in binding to the tested targets, despite the predicted difference in binding specificity based on the thioester catalytic site. The participation of C4-1 in the classical and lectin pathways of complement activation was also explored using pathway-specific activating enzyme complexes, C1r/s and MBL-MASP2. As a result, C4-1 can be activated in both the classical and the lectin pathways, at higher efficiency in the classical pathway. Taken together, the present results imply that both C4-1 and C4-2 isotypes are fully functional in the complement activation cascades, probably playing comparable roles in innate immunity.